A Analisis Pengaruh Sektor Industri Halal Terhadap Pertumbuhan Ekonomi di Negara-Negara Anggota OKI - Ardiansah, Roni (Jurnal Keuangan dan Perbankan Syariah, 2024)
The aim of this research is to examine and analyze the influence of the halal industrial sector on economic growth in the long term and short term in OIC member countries. This research uses a quantitative approach, and the method used is the Vector Error Correction Model (VECM) to determine the long-term and short-term effects between variables. The data source for this research is secondary data, panel data from 2014 to 2023 obtained from DinarStandard and the World Bank. Data processing tools use the E Views-10 statistical application. The findings of this research show that in the long term Halal Fashion and Islamic Entertainment Media have a significant positive effect on economic growth, with t-statistics of 8.308 and 6.372. Halal Food, Cosmetics and Halal Medicines have a significant negative effect on economic growth, with t-statistics of -4.012 and -3.829. Then, Islamic Finance and Halal Tourism do not have a significant effect on economic growth, with t-statistics of 0.893 and -0.910. Then, in the short term Islamic Finance has a significant positive effect on economic growth, with a t-Statistic of 3.058. Meanwhile, Halal Food, Halal Tourism, Halal Fashion, Islamic Media and Entertainment, Halal Cosmetics and Medicines do not have a significant effect on economic growth, with t-statistics of 0.506, 1.865, 0.256, -1.319 and -1.111. In this research, data analysis uses the Vector Error Correction Model (VECM) method so that the research results obtained are broader, namely in the long term and short term. This research uses more panel data than several previous studies.